1988
DOI: 10.1029/jb093ib11p13407
|View full text |Cite
|
Sign up to set email alerts
|

Source Process of the Great 1977 Sumba Earthquake

Abstract: In order to investigate the applicability of the asperity model to intraplate earthquakes we have studied the rupture process of the great 1977 Sumba normal‐faulting earthquake (Mw=8.2–8.3), one of the largest earthquakes since 1963. This event has been variously interpreted as a plate detachment event (i.e., rupture through the entire lithosphere) or a shallow plate‐bending event. We have analyzed long‐period body waves in order to determine the spatiotemporal rupture characteristics, including the depth exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…In contrast, SILVER and JORDAN (1983) obtained a centroid depth shallower than 20 km from the moment spectra. Consistent with this centroid depth, FITCH et al (1981) found that the depth range of major aftershocks is 8-24 km and LYNNES andLAY (1988) obtained the source extent not deeper than 35 km from the analysis of long-period body waves.…”
Section: The 1933 Sanriku Earthquakesupporting
confidence: 52%
“…In contrast, SILVER and JORDAN (1983) obtained a centroid depth shallower than 20 km from the moment spectra. Consistent with this centroid depth, FITCH et al (1981) found that the depth range of major aftershocks is 8-24 km and LYNNES andLAY (1988) obtained the source extent not deeper than 35 km from the analysis of long-period body waves.…”
Section: The 1933 Sanriku Earthquakesupporting
confidence: 52%
“…Typically, the largest magnitude trench-slope aftershocks are much smaller than the underthrusting mainshocks, and the primary interest in these events has been for quantifying aspects of the stress variations associated with the seismic cycle of megathrust faults and the relative importance of dynamic and bending stresses (e.g., Dmowska et al, 1988;Lay et al, 1989;Taylor et al, 1996). However, some great extensional faulting events have happened in the outer trench slope environment with no proximate large thrust event, such as the 1977 Sumba (M w 8.4) (Lynnes and Lay, 1988) and 2009 Samoa (M w 8.1) (Lay et al, 2010) earthquakes which occurred seaward of what appear to be seismically weakly-coupled subduction zones. For these latter events, slab-pull/bending stresses appear to play important roles, with no obvious influence from interplate seismic stress cycles, although as yet undetected slow earthquakes on the megathrust may occur in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…Sumba earthquake (Spence, 1986;Lynnes & Lay, 1988), or after a preceding megathrust event has ruptured the shallow coupled zone, as for the 1933 M W 8.4 Sanriku earthquake (Kanamori, 1971) (Christensen & Lay, 1988).…”
Section: Introductionmentioning
confidence: 99%